(untitled) (African Journal of Biomedical Research, 2023)
One of the most challenging periods of every woman is the menopausal phase when changes occur both physically and emotionally. Changes in nutritional status can be a concern, which may have direct or indirect effect on the menopausal woman. This cross-sectional study examined the relationship between Nutritional Status and postmenopausal complications among adult women. The survey was conducted on 278 menopausal women aged between 45-65 years resident in Ogbomoso North and Ogbomoso South Local Government Areas of Oyo State. Socio-demographic and anthropometrics data were collected using self-administered questionnaire. Energy and nutrient intake were recorded through 24-hour dietary food recall. Descriptive statistics and Chi square test at α0.05 were done using SPSS version 21. Using the Body Mass Index (BMI) categorization, 16.5%, 37.8%, 43.2% and 2.5% of the respondents had normal weight, were overweight, obese, and morbidly obese respectively. The most common diseases during the menopausal period were hypertension (23.9%) and diabetes (6.5%). Mean calcium and potassium intake were less than Recommended Daily Allowance (RDA) at 139.35±6.61mg/day and 633.90±31.39mg/day respectively. However, the consumption of carbohydrates, protein and fat were found to be in excess. This imbalance in nutrients intake and other lifestyle habits yielded in increased BMI which was associated with many menopausal complications. BMI was significantly associated with marital status, hypertension, insomnia, hot flushing, bloated feeling, irregular heartbeat, fatigue, constipation, waist, hip and joint pain. Interventions on healthy eating, healthy lifestyle which are necessary to promote and improve healthy aging and to overcome the postmenopausal problem are recommended.